Answer:
decay function
Step-by-step explanation:
took the usa test prep
The sum of two numbers increased by 5
Answer:
(x+y)+5
Step-by-step explanation:
To solve this, all you need is two variables to represent the 2 numbers. In this case, I used x and y. After that it says the sum of those 2 numbers increased by 5. All you need to know about that is that after x+y is done, you need to increase it by 5. So in this case,
(x+y)=5 satisfies the statement.
What is the value of the rational expression when x=-2? -7 -9 9 7
The value of the rational expression [tex]\frac{2x^2+5x+9}{x^2+2x-1}[/tex] when x =-2 is -7
What is ration expression?A rational expression is an expression that can be written in the form of a ratio of two polynomial expressions. Specifically, it is a fraction in which the numerator and denominator are both polynomials.
How to find value of rational expression?To find the value of the rational expression when x=-2, we substitute -2 for x in the expression and simplify:
[tex]\frac{2x^2 + 5x + 9}{x^2 + 2x - 1}[/tex]
= [tex]\frac{(2(-2)^2 + 5(-2) + 9)}{((-2)^2 + 2(-2) - 1)}[/tex]
=[tex]\frac{8 - 10 + 9}{4 - 4 - 1}[/tex]
= [tex]\frac{7}{-1}[/tex]
= -7
Therefore, the value of the rational expression [tex]\frac{2x^2+5x+9}{x^2+2x-1}[/tex] when x =-2 is -7.
Learn about rational expression here https://brainly.com/question/29061047
The question is incomplete, see full details in the attached image.
The value of the expression is Option a. -7.
To find the value of the rational expression (2x² + 5x + 9) / (x² + 2x - 1) when x = -2, we need to substitute -2 into the expression.
First, let's calculate the numerator:
2(-2)² + 5(-2) + 9= 2(4) -10 + 9= 8 - 10 + 9= 7Next, we calculate the denominator:
(-2)² + 2(-2) - 1= 4 - 4 - 1= -1Now, we divide the numerator by the denominator:
= 7 / (-1)= -7So, the value of the rational expression when x = -2 is -7. Therefore, the correct answer is Option a. -7.
Complete question:
What is the value of the rational expression (2x²+5x+9)/x²+2x-1 when x=-2
a. -7
b. -9
c. 9
d. 7
The measure of arc BD is __.
The measure of arc ADB is __.
The measure of arc ABC is __.
PLEASE HELP. URGENT!! ASAP
- The measure of arc [tex]\( BD \)[/tex] is 260°.
- The measure of arc [tex]\( ADB \)[/tex] should be 320° (corrected).
- The measure of arc [tex]\( ABC \)[/tex] is 80°.
To find the measure of each arc in the circle, we need to remember that the total degrees in any circle is 360°. The diagram shows a circle with specific arcs and angles labeled.
Here are the steps to find each arc's measure:
1. Measure of arc [tex]\( BD \)[/tex]:
- Arc [tex]\( BD \)[/tex] is opposite the central angle [tex]\( \angle BRD \)[/tex], which is not directly given.
- Since [tex]\( \angle BRC \)[/tex] is 40° and [tex]\( \angle CRD \)[/tex] is 60°, then [tex]\( \angle BRD = 360° - (\angle BRC + \angle CRD) \)[/tex].
- Calculating [tex]\( \angle BRD \)[/tex] gives [tex]\( 360° - (40° + 60°) = 260° \)[/tex].
- Therefore, the measure of arc \( BD \) is 260°.
2. Measure of arc [tex]\( ADB \)[/tex]:
- Arc [tex]\( ADB \)[/tex] includes arcs [tex]\( AD \)[/tex] and [tex]\( DB \)[/tex].
- We already know [tex]\( DB \)[/tex] is 260°.
- [tex]\( AD \)[/tex] is opposite the central angle [tex]\( \angle ARD \)[/tex], which is given as 120°.
- Adding them together, the measure of arc [tex]\( ADB = \angle ARD + \angle BRD = 120° + 260° = 380° \).[/tex]
- This exceeds 360°, which suggests an error. Since [tex]\( AD \)[/tex] and [tex]\( BD \)[/tex] are parts of the circle that add up to its whole circumference, they should add up to 360°, not more. Hence, [tex]\( ADB \)[/tex] should be [tex]\( 360° - \angle BCD \)[/tex] which is 360° - 40° = 320°.
3. Measure of arc [tex]\( ABC \)[/tex]:
- Arc [tex]\( ABC \)[/tex] includes arcs [tex]\( AB \)[/tex] and [tex]\( BC \).[/tex]
- [tex]\( BC \)[/tex] is opposite the central angle [tex]\( \angle BRC \)[/tex], which is given as 40°.
- [tex]\( AB \)[/tex] is the rest of the circle not included in \( ADB \), so [tex]\( AB = 360° - \angle ADB \)[/tex].
- Since we've found an inconsistency with [tex]\( ADB \)[/tex], we should instead calculate [tex]\( AB \)[/tex] as [tex]\( 360° - (BD + CD) = 360° - (260° + 60°) = 40° \).[/tex]
- Adding \( AB \) and \( BC \), the measure of arc [tex]\( ABC = AB + BC = 40° + 40° = 80° \).[/tex]
There seems to be an error with the measure of arc [tex]\( ADB \)[/tex] as calculated before. Arcs [tex]\( AD \)[/tex] and [tex]\( DB \)[/tex] should add up to 360° because they complete the circle together. It's also worth noting that in a properly drawn circle, the sum of the measures of arcs [tex]\( BC \)[/tex], [tex]\( CD \)[/tex], and [tex]\( DA \)[/tex]should add up to 360°. If [tex]\( BC \)[/tex] is 40° and [tex]\( CD \)[/tex] is 60°, then [tex]\( DA \)[/tex] should be 360° - (40° + 60°) = 260°, not 120°. This discrepancy suggests there may be a mistake in the given information or a misinterpretation of the diagram.
To summarize, given the information provided:
- The measure of arc [tex]\( BD \)[/tex] is 260°.
- The measure of arc [tex]\( ADB \)[/tex] should be 320° (corrected).
- The measure of arc [tex]\( ABC \)[/tex] is 80°.
Have three witches each holding a broom and a spoon. Witches say witch plus witch plus witch =45. Three brooms say broom plus broom plus a broom =21 and three spoons say spoon plus spoon plus spoon = 12 then final question is a plain witch plus broom x spoon equal a ? What’s answer?
Answer:
a=43
Step-by-step explanation:
w+w+w= 45 which means 15+15+15=45
b+b+b=21 which means 7+7+7=21
s+s+s=12 which means 4+4+4=12
w+b×s= a which means 15+7×4= 43
(hope this helps)
Answer:
The answer to the question is 43
Step-by-step explanation:
Let us recall the values from the following question stated:
Three witches each holds a broom and a spoon, saying plus witch plus witch = 45
Three brooms say broom plus broom plus a broom at = 21
Three spoons say spoon plus spoon plus = 21
Now, let us find when a plain witch plus broom x spoon
Then,
Three witches = 45, resulting to 15+15+15=45
Three brooms (b+b+b) which is =21 or 7+7+7=21
Three spoons (s+s+s) is =12 or 4+4+4=12
we make use of multiplication for the witches, the brooms, and the spoons
Therefore
w+b×s= a, which is 15+7×4= 43
In a sample of voters in Harrisburg, 18 out of 25 favored creating a new shopping center. If 50,000 people vote in the next Harrisburg election, how many are likely to vote in favor of the new shopping center based on this sample?
Answer:
36,000 people are likely to vote in favour of the new shopping centre
Step-by-step explanation:
Given
Population = 50,000
Total Sample = 25
18 favoured opening a new shopping centre
Required
Likely number of people to vote in favor of the new shopping center.
First, we need to represent the sample in proportion.
Let p represent the proportion
Since 18 out of 25 are in support of opening a new center,
p = 18/25
Having solved for the proportion,the next step is to calculate the expected number of people.
This is calculated by multiplying p by the total population.
Given that population = 50,000
The expected outcome = 18/25 * 50,000
Expected outcome = 18 * 2,000
Expected outcome = 36,000
Hence, 36,000 people are likely to vote in favour of the new shopping centre
Answer:
36,000 voters
Step-by-step explanation:
Here we have a question on proportion
Proportion of voters that favored creating a new shopping center = 18/25
That is the point estimate of voters that favored creating a new shopping center = 18/25
Therefore, among 50,000 voters in Harrisburg the number of voters that are likely to vote in favor of the new shopping center, based on the point estimate of the sample is given by the following expression;
18/25 × 50,000 = 36,000 voters.
172.7=3.14d
Solve for d
Answer:
55
Step-by-step explanation:
Divide both sides by 3.14 to get d by itself.
172.7 / 3.14 = 55 = d
A sphere has been placed inside an cylinder with the same dimensions;both have a radius of 6cm,and a height of 12cm How many cubic centimeters of space does the sphere fill not fill up. A.432pi cm B.72 pi cm C.288 pi cm D.144 pi cm
Answer:
D
Step-by-step explanation:
Final answer:
To find the cubic centimeters of space not filled by the sphere in the cylinder, subtract the volume of the sphere (288π cm³) from the volume of the cylinder (432π cm³), yielding 144π cm³. Therefore, the correct answer is D. 144π cm³.
Explanation:
To determine how many cubic centimeters of space the sphere does not fill in the cylinder, we first need to calculate the volume of the cylinder and then subtract the volume of the sphere from it.
The volume of a cylinder is given by the formula V = πr²h, where r is the radius and h is the height. In this case, with a radius of 6 cm and height of 12 cm, the volume is:
[tex]V_{cylinder}[/tex] = π × (6 cm)² × 12 cm = 432π cm³.
The volume of a sphere is given by the formula V = 4/3 πr³. With a radius of 6 cm, the volume is:
[tex]V_{sphere[/tex] = 4/3 π × (6 cm)³ = 288π cm³.
The space the sphere does not fill up in the cylinder is:
Space not filled = [tex]V_{cylinder}[/tex] - [tex]V_{sphere[/tex] = 432π cm³ - 288π cm³ = 144π cm³.
Therefore, the answer is D. 144π cm³.
Which rules of exponents will be used to evaluate this expression? Check all that apply.
StartFraction left-brace (negative 8) Superscript 4 Baseline right-brace Superscript negative 5 Baseline Over (negative 8) Superscript 6 Baseline EndFraction
product of powers
quotient of powers
power of a power
power of a product
negative exponent
zero exponent
Answer:
quotient of powers power of a power negative exponentStep-by-step explanation:
Given
( -8⁴)⁻⁵ / ( -8⁶)Evaluating:
( -8⁴)⁻⁵ / ( -8⁶) =( -8⁴ˣ⁻⁵) / ( -8⁶) = ⇒ Power of a power (nᵃ)ᵇ = nᵃᵇ(-8⁻²⁰)/( -8⁶) =8⁻²⁰⁻⁶ = ⇒ Quotient of powers nᵃ/nᵇ = nᵃ⁻ᵇ8⁻²⁶ = 1/8²⁶ ⇒ Negative exponent n⁻ᵃ = 1 / nᵃUsed rules:
quotient of powers power of a power negative exponentAnswer:
B-quotient of powers
C-power of a power
E-negative exponent
Step-by-step explanation:
PLEASE SIMPLIFY THESE
a) 2.56x+0.14−1.87x
b) 7.32a+2.1∙(2.7−18a)
c) 0.12x+0.34y+0.98x−3.35y
THANK YOU
Answer:
a. 0.69x + 0.14
b. 5.67 - 30.48a
c. 1.1x - 3.01y
Step-by-step explanation:
a) 2.56x + 0.14 − 1.87x
To simplify this algebraic expression, you start by collecting like terms;
2.56x − 1.87x + 0.14
Then perform arithmetic operation
0.69x + 0.14
b) 7.32a + 2.1 (2.7 − 18a)
Here; first, the bracket must be opened
To open the bracket; each expression in the bracket is multiplied by 2.1. This leaves us with
7.32a + 2.1 * 2.7 − 2.1 * 18a
7.32a + 5.67 - 37.8a
Then, you collect like terms
7.32a - 37.8a + 5.67
Then perform arithmetic operation
-30.48a + 5.67
Rearrange
5.67 - 30.48a
c) 0.12x + 0.34y + 0.98x − 3.35y
Here, you start by collecting like terms
0.12x + 0.98x + 0.34y − 3.35y
Then perform arithmetic operation
1.1x - 3.01y
Which is an equivalent expression to b^-3•n^-6?
1/n^9
1/n^-9
1/n^-18
1/n^18
(they are fractions) PLEASE ANSWER ASAP. NEED IT
Answer:
I think you may have made a mistake when entering the original equation. Assuming you meant to put "n" where you put "b" as the variable, the answer is b) 1/n^-9
Step-by-step explanation:
You simply add exponents when multiplying them if they have the same base. Thus -3 + -6 is -9.
what is one difference between Geometric and Arithmetic Sequence
An arithmetic sequence is a sequence with two consecutive terms that are constant, while a geometric sequence is a sequence where the ratio between two consecutive terms constant.
Diego has a skateboard, scooter, bike and go-cart. he wants to know which vehicle, is the fastest. a friend records how far diego traveles on each vehicle in 5 seconds. for each vehicle, diego travels as fast as he can along a straight path vehicle skateboard path=90 feet scooter=1,020 bike=4,800 centimeters go kart=0.03 kilometers a.100 inches equal 245 centimeters whatis the distance each vehicle traveled in centimers? ?
Answer:
1. Skateboard: 2,743.2. Scooter: 2,590.8. Bike: 4,800. Go-cart: 3,000.
After converting all distances to centimeters, it's clear that Diego's bike traveled the furthest (4800 cm) in 5 seconds, making it the fastest.
Explanation:Understanding the speed of Diego's vehicles requires us to convert the distances all to the same unit, centimeters. First, we know that 1 foot equals 30.48 cm. Therefore, the skateboard traveled 90 feet * 30.48 cm/foot = 2743.2 cm. The scooter traveled 1020 feet, which means it traveled 1020 feet * 30.48 cm/foot = 31,089.6 cm. The bike traveled 4800 cm, so no conversion is needed for this vehicle. Lastly, 1 kilometer equals 100,000 cm, meaning the go-kart traveled 0.03 kilometers * 100,000 cm/kilometer = 3,000 cm. Now that we have all the distances in the same unit, we can compare and state that the bike traveled the furthest in 5 seconds, making it the fastest.
Learn more about Speed Comparison here:https://brainly.com/question/41515175
#SPJ12
At Marvin's Motorcycle's a pair of gloves sell for $85. Marvin purchases them from the manufacturer for $50. What is the percent markup on the gloves?
Plz help! 10 points
The water temperature required for a certain manufacturing process is 134°F. However, the process allows for a variation of 7°F in the water temperature.
If x represents the water temperature, which inequality describes the situation? What is the range of water temperatures that is allowed for this process?
Answer:
The temperature that represents a smaller value would be the one with negative eighty (or -80) degrees Fahrenheit. Although it is negative, the value of 80 does not mean it has a smaller value as to 134 degrees. It is just that the difference between the absolute values of the two show that 134 degrees Fahrenheit has a bigger value.
Step-by-step explanation:
Answer:
|X-134| < 7
_
Step-by-step explanation:
3. Of the three expressions shown, which two
are equivalent?
3+2(9 + 2n) 7(3 + 4n) 21 + 4n
Answer:
the answer would be the first and last equation
Step-by-step explanation:
both equations equal 21+4n
Final answer:
After simplifying the expressions, it's found that 3 + 2(9 + 2n) simplifies to 21 + 4n, and the third expression is exactly 21 + 4n. These two expressions are equivalent.
Explanation:
To determine which two of the three expressions are equivalent, we need to simplify each expression and compare them.
Let's simplify each expression:
3 + 2(9 + 2n) = 3 + 18 + 4n = 21 + 4n
7(3 + 4n) = 21 + 28n
21 + 4n = 21 + 4n
Now, we can compare them:
The first expression, after simplification, becomes 21 + 4n.
The second expression is 21 + 28n, which is not equivalent to the first.
The third expression is exactly 21 + 4n, which is equivalent to the first expression.
So, the expressions 3 + 2(9 + 2n) and 21 + 4n are equivalent.
If Y=X2 -2x - 3 , what is y when x =3
As per quadratic equation, the value of 'y' for [tex]x = 3[/tex] is 0.
What is a quadratic equation?"A quadratic equation is an algebraic equation of the second degree in 'x'. The quadratic equation in its standard form is [tex]ax^{2} + bx + c = 0[/tex], where 'a' and 'b' are the coefficients, 'x; is the variable, and 'c' is the constant term."
Given quadratic equation is:
[tex]y = x^{2} -2x - 3[/tex]
When [tex]x = 3[/tex], the value of 'y' is:
[tex]= 3^{2} -2(3) - 3\\= 9 - 6 - 3\\= 0[/tex]
Learn more about quadratic equation here: https://brainly.com/question/2263981
#SPJ3
When [tex]\( x = 3 \)[/tex] is substituted into [tex]\( y = x^2 - 2x - 3 \)[/tex], it yields y = 0 after simplification.
To find the value of y when x = 3 in the equation [tex]\( y = x^2 - 2x - 3 \),[/tex]substitute [tex]\( x = 3 \)[/tex] into the equation and solve for (y):
[tex]\[ y = (3)^2 - 2(3) - 3 \]\[ y = 9 - 6 - 3 \]\[ y = 0 \][/tex]
So, when [tex]\( x = 3 \), \( y = 0 \).[/tex]
If tan(θ) = cot(40°), what is θ?
Answer:
50 lol
Step-by-step explanation:
Answer:
Θ = 50°
Step-by-step explanation:
Using the cofunction identity
tan(90 - x)° = cotx°
Given
cot40°, then
tan Θ = tan(90 - 40)° = tan50°
Thus Θ = 50°
how do i find the area of a trapezoid (pictures provided)
Answer:
(10x - 5) square units.
Step-by-step explanation:
Let the lengths of equal sides be x units.
Hence, AB + AD + DC = x + x + x = 3x
Therefore, BC = 3x - 2
[tex]Area \: of \: trapezoid \\ = \frac{1}{2} (AD + BC) \times 5 \\ = \frac{1}{2} (x + 3x - 2) \times 5 \\ = \frac{1}{2} (4x - 2) \times 5 \\ = \frac{1}{2} \times 2 (2x - 1) \times 5 \\ = (2x - 1) \times 5 \\ = (10x - 5) \: {units}^{2} [/tex]
Two nickels are what fraction of a dollar?
Answer:
1/10
Step-by-step explanation:
Answer:
2/20?
Step-by-step explanation:
Which describes the calculations that could be used to solve this problem?
Tina has 37 oranges to pack into boxes and bags. She has one box that will hold 13 oranges. She will put the rest of the oranges into bags with 4 oranges in each bag.
How many bags of oranges will Tina be able to fill?
A.
Subtract 37 – 13. Then divide the difference by 4.
B.
Add 37 + 13. Then divide the sum by 4.
C.
Add 4 + 13. Then add 37 to the sum.
D.
Subtract 37 – 13. Then multiply the difference by 4.
Answer:
A.
Subtract 37 – 13. Then divide the difference by 4.
Step-by-step explanation:
After the box:
37 - 13 left
No. of bags:
(37 - 13)/4
Point A, located at (-5, 1) is translated. Point A' is located at (6, 1). What was the translation?
11 units up
11 units down
11 units right
11 units left
Answer:
11 units right
Step-by-step explanation:
11 units right
from A (-5, 1) to A' (6, 1)
(-5 + 11, 1 ) = (6, 1)
Answer:ll units right
Step-by-step explanation:
The expression 3.5m + 20p gives the amount of money, in dollars, a bakery makes from selling m
muffins and p pies. How much money does the bakery make from selling 5 muffins and 3 pies?
A. $37.50
B. $77.50
C. $63.50
D. $110.50
Determine which diagram could be used to prove AABC - AEDC using similarity transformations,
The diagram which could be used to prove AABC - AEDC using similarity transformations is A.
What are congruent triangles?Suppose it is given that two triangles ΔABC ≅ ΔDEF
Then that means ΔABC and ΔDEF are congruent. Congruent triangles; are exact same triangles, but they might be placed at different positions.
The order in which the congruency is written matters.
For ΔABC ≅ ΔDEF, we have all of their corresponding elements like angle and sides congruent.
Thus, we get:
[tex]\rm m\angle A = m\angle D \: or \: \: \angle A \cong \angle D \angle B = \angle E\\\\\rm m\angle B = m\angle E \: or \: \: \angle B \cong \angle E \\\\\rm m\angle C = m\angle F \: or \: \: \angle C \cong \angle F \\\\\rm |AB| = |DE| \: \: or \: \: AB \cong DE\\\\\rm |AC| = |DF| \: \: or \: \: AC \cong DF\\\\\rm |BC| = |EF| \: \: or \: \: BC \cong EF[/tex]
(|AB| denotes length of line segment AB, and so on for others).
We are given that;
The three figures in the picture
Now, in first figure
Angle BAC= Angle CED
(given)
Angle BCA= Angle ECD
(interior opposite angles)
So, both triangles are congruent
Therefore, by congruent triangles answer will be figure A.
Learn more about congruent triangles here:
https://brainly.com/question/16921692
#SPJ7
Help me ok thank you
Answer:
-422
Step-by-step explanation:
The elevation of the Dead Sea is 422 meters below sea level, meaning that it is -422.
PLEASE ANSWER ASAP!!!
Find the volume of the figure. Round to the nearest tenth, if necessary.
a regular hexagonal prism with base area 25 in? and height 8 in.
The volume of the figure is
Answer:
The volume of the figure is since you have to do width times height so 25 times 8 which would be 200 as your answer.
Hope it helps
It costs $25 to buy 5 sandwiches from a vending machine. At this rate, what is the cost for 8 sandwiches?
Answer:
x = 40
Step-by-step explanation:
We can use a ratio to solve
$25 x
------- = --------
5 8
Using cross products
25*8 = 5x
200 = 5x
Divide each side by 5
200/5 = 5x/5
40 =x
Examples of skew lines
Answer:
An example of skew lines are the sidewalk in front of a house and a line running across the top edge of a side of a house.
Step-by-step explanation:
:D
Final answer:
Skew lines are lines that do not intersect and are not parallel. Examples include a ladder leaning against a wall, non-parallel railway tracks, and a pencil and a ruler placed randomly on a table.
Explanation:
Skew lines are lines that do not intersect and are not parallel. They are in the same plane but do not lie on the same line. One example of skew lines is a ladder leaning against a wall. The ladder and the wall are in the same plane, but they do not intersect and are not parallel.
Another example of skew lines is a pair of non-parallel railway tracks. The tracks are in the same plane, but they do not intersect and are not parallel.
Finally, a pencil and a ruler placed randomly on a table can also be considered as skew lines. They are in the same plane, but they do not intersect and are not parallel.
Isabelle stacked two wooden blocks as shown. What is the volume of the stacked blocks?
Part 1:-
=> Volume of cuboid = lbh
=> Volume of cuboid = 3 × 16 × 2
=> Volume of cuboid = 6 × 16
=> Volume of cuboid = 96 cm³
Part 2:-
=> Volume of traingle = bh
=> Volume of traingle = 10 × 4
=> Volume of traingle = 40 cm³
Now,
→ Total Volume = Vol. of cuboid + Vol. of traingle
→ Total Volume = 96 + 40
→ Total Volume = 136 cm³
Thanks!
Let me know if answer is wrong.
Two vertices of a rectangle are shown. If AC is a diagonal of the rectangle, and two other vertices of the rectangle, B and D, lie on the nodes of the grid, then how many rectangles have vertices A, B, C and D?
9514 1404 393
Answer:
3
Step-by-step explanation:
There are 3 grid nodes suitable for vertex D that lie the same distance from the center of the rectangle as points A and C.
3 rectangles have vertices ABCD that lie on grid nodes.
3 x + 9 = box If the equation has no solution, which expression can be written in the box on the other side of the equation?
Answer:
Step-by-step explanation
3x+9=?
subtract 9 from both sides
3x=-9
divide by 3
x=-3
Now plug it in to find your soultion that is not correct
3(-3)+9=
-9+9=
0
Answer:
To find the expression for the box, we need to simplify the equation. Let's break it down step by step:
3 (x + 1) + 9 = box
First, distribute the 3 to the terms inside the parentheses:
3x + 3 + 9 = box
Next, combine like terms:
3x + 12 = box
Now, we can compare the simplified equation to the given expressions:
3 (x + 4)
2 (x + 6) + x
4(x – 3) – x
3 (x + 1) + 9
We are looking for an expression that matches our simplified equation, which is 3x + 12. By comparing the expressions, we can see that 3 (x + 1) + 9 is the same as 3x + 12.
Therefore, the expression that can be written in the box is 3 (x + 1) + 9.
Please give me brainliest!